MANAGEMENT OF NATURAL RESOURCES IN THE CENTRAL ASIAN REGION - Khikmat, Mukhammadjon; Znotiņa, Daina (Journal of Regional Economic and Social Development, 2022)
The term "natural resources" refers to both the natural and socio-economic realms. Natural resources - bodies and forces of nature - are linked to ensure close interaction in the process of nature management. Currently, this specific region has some vulnerable issues such as biodiversity loss and land degradation that are connected with poor resource management. The activities of modern society are followed by enormous changes in nature, which are reflected in the Earth's exterior appearance as well as the states of geosystems. Modern production is distinguished by the inclusion of significant reserves of natural resource potential. However, its participation and application are ineffective. Sustainable development necessitates the management of natural resources in a sustainable and integrated manner. The main purpose of the work is to investigate the main natural resources of the Central Asian region, and to show the cost of poor management. The methods that were used are synthesis, analysis, comparison method, and forecasting method. The novelty of the research is the attention paid to the mismanagement of natural resources in a specific region.